2021
DOI: 10.5194/nhess-2021-159
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The importance of raising risk awareness: lessons learned about risk awareness sessions from the Mediterranean region (North Morocco and West Sardinia, Italy)

Abstract: Abstract. Risk management is used in societies to mitigate the potentially dramatic effects of natural hazards. Local authorities and managers use different indicators in elaborating rescue and urbanism plans, which are not always efficient in reducing impact in the time of the crisis. This highlights society’s vulnerability in the particular context of global environmental and climate changes. This interdisciplinary research aimed at identifying reliable risk indicators and societal responses regarding natura… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…In line with numerous studies (Ivčevi c et al, 2021;Roder et al, 2016), this research has proven the great significance of risk awareness as the determinant of risk perception. As mentioned, risk awareness had the greatest impact on risk perception; however, this was to a large extent complemented by the individual's direct experience of the consequences of the extreme weather (namely low to significant house/property damage caused by a storm, gale, heavy rain, hail) (Gao et al, 2020).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In line with numerous studies (Ivčevi c et al, 2021;Roder et al, 2016), this research has proven the great significance of risk awareness as the determinant of risk perception. As mentioned, risk awareness had the greatest impact on risk perception; however, this was to a large extent complemented by the individual's direct experience of the consequences of the extreme weather (namely low to significant house/property damage caused by a storm, gale, heavy rain, hail) (Gao et al, 2020).…”
Section: Discussionsupporting
confidence: 77%
“…As stressed by Slovic and Weber (2002) regarding building risk awareness, experience works in parallel with knowledge. The latter is here understood both as the indigenous wisdom and outside information as well as its uptake (Ivčevi c et al, 2021). In this study, personal experience is considered through basic characteristics such as severity/seriousness, directness/proximity and frequency.…”
Section: Risk Perception Factors Of Extreme Weather Eventsmentioning
confidence: 99%
“…Participating in awareness-raising activities showed significant and positive correlation with the reported mitigation strategies of using public transport more often and with eating more organic food and less meat. However, although risk awareness has been shown in many studies as not being enough to implement risk mitigation strategies (as is demonstrated by the low levels of mitigation measures reported), it remains an important first step to do so and for ultimately building societal resilience, as discussed in [4]. The question that is posed is how to reduce the gap between having hazard knowledge and using this knowledge to implement precautionary behaviors?…”
Section: Discussionmentioning
confidence: 99%
“…Understanding risk perception, and particularly risk awareness, is of major importance in risk management. It can improve efficient risk communication and inform mitigation strategies to reduce vulnerability and enhance resilience [1][2][4][5]. In light of the accelerating climate change processes, a better understanding of the role that risk perception has in shaping adaptive behavior is needed in order to cope with extreme weather events and enhance societal resilience [5].…”
Section: Introductionmentioning
confidence: 99%
“…Awareness of the population is essential in risk management because it influences risk perception, motivating preventive behavior (Gibson, 2003;Haynes et al, 2008;Luís et al, 2016). Despite the above, few studies have conceptually differentiated risk awareness from risk perception (Bandecchi et al, 2019;Ivčević et al, 2020Ivčević et al, , 2021. In some cases, both concepts have been considered synonymous (Bradford et al, 2012;Raaijmakers et al, 2008), but risk awareness has also been measured as part of risk perception (Pagneux et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%